2022
DOI: 10.1002/cbic.202200398
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II) Polypyridyl Complexes Containing Simple Dioxo Ligands: a Structure‐Activity Relationship Study Shows the Importance of the Charge

Abstract: Cancer is one of the main causes of death worldwide. Platinum complexes (i. e., cisplatin, carboplatin, and others) are currently heavily used for the treatment of different types of cancer, but unwanted effects occur. Ruthenium complexes have been shown to be potential promising alternatives to these metalbased drugs. In this work, we performed a structure-activity relationship (SAR) study on two small series of Ru(II) polypyridyl complexes of the type [Ru(L1) 2 (O^O)]Cl n (3-8), where L1 is 4,7diphenyl-1,10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Ru( ii ) molecules containing dip ligands have been shown to induce mitochondrial dysfunction, 62 due to their lipophilicity and cationic charge. 63 As compound 2 contains the dip ligand, its impact on mitochondrial function was assessed. The Seahorse MitoStress profile for cells pre-treated with 2 at 6× the IC 50 value did not show any significant difference in response compared to the vehicle control ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ru( ii ) molecules containing dip ligands have been shown to induce mitochondrial dysfunction, 62 due to their lipophilicity and cationic charge. 63 As compound 2 contains the dip ligand, its impact on mitochondrial function was assessed. The Seahorse MitoStress profile for cells pre-treated with 2 at 6× the IC 50 value did not show any significant difference in response compared to the vehicle control ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[116] SAR studies led on ruthenium(II) polypyridyl complexes (22-24; Figure 12) also showed that a slight change of dioxo ligand was enough to change the preferential localization of complex 24 to the mitochondria compared to complexes 22 and 23. [113,114] It is unclear whether the molecular target of all these compounds stayed the same, but an increase in lipophilicity is likely to be responsible for the higher cellular uptake observed and the mitochondrial localization.…”
Section: The Importance Of Lipophilicity and Its Balancementioning
confidence: 99%
“…However, a loss of nuclear localization was observed. [ 114 ] Barton and co‐workers reported a rhodium(III) metallo‐insertor that targets DNA mismatches and displays selectivity towards MMR‐deficient cells ( 25a ; Figure 12). [ 115 ] As expected, the complex was found to accumulate in the nucleus due to its DNA‐binding affinity, but interestingly, the introduction of a methyl substituent instead of a hydroxyl on two of the ligands redirected the resulting complex 25b to the mitochondria (Figure 12).…”
Section: Nucleus‐targeting Strategies For Metal Complexesmentioning
confidence: 99%
“…These ligands provide multiple features for the modulation of physicochemical properties due to their redox non-innocent nature, electronic effects, variable charge and kinetic labilities, lipophilicities, etc., which are important parameters towards dictating the pharmacokinetic profiles of the designed cytotoxic Ru(II) complexes. 14 A. Notaro et al reported an in-depth structureactivity relationship (SAR)-based cytotoxicity study for a series of [Ru(DIP) 2 (sq/cat)] complexes via tuning the electronic structure of the dioxo (η 2 -O^O) ligands showing excellent in vitro and in vivo cytotoxicity involving multi-cellular targets appropriate to overcome acquired drug resistance. 15,16 Oxalic acid is opted as a ligand considering its biocompatibility, broad applications in industry and medicine, etc.…”
Section: Introductionmentioning
confidence: 99%